The Changing Landscape of Autoimmune Hemolytic Anemia - Barcellini, Wilma; Fattizzo, Bruno (Frontiers in Immunology, 2020)
Autoimmune hemolytic anemia (AIHA) is a greatly heterogeneous disease due to autoantibodies directed against erythrocytes, with or without complement activation. The clinical picture ranges from mild/compensated to life-threatening anemia, depending on the antibody’s thermal amplitude, isotype and ability to fix complement, as well as on bone marrow compensation. Since few years ago, steroids, immunesuppressants and splenectomy have been the mainstay of treatment. More recently, several target therapies are increasingly used in the clinical practice or under development in clinical trials (sutimlimab, sirolimus, parsaclisib, fostamatinib, other complement inhibitors and anti-neonatal Fc receptor agents). This has led to the accumulation of refractory/relapsed cases that often represent a clinical challenge. Moreover, the availability of several drugs acting on the different pathophysiologic mechanisms of the disease pinpoints the need to harness therapy. In particular, it is advisable to define the best choice, sequence and/or combination of drugs during the different phases of the disease. In particular relapsed/refractory cases may resemble pre-myelodysplastic or bone marrow failure syndromes, suggesting a careful use of immunosuppressants, and vice versa advising bone marrow immunomodulating/stimulating agents. A peculiar setting is AIHA after autologous and allogeneic hematopoietic stem cell transplantation, which is increasingly reported. These cases are generally severe and refractory to standard therapy, and have high mortality. AIHAs may be primary/idiopathic or secondary to infections, autoimmune diseases, malignancies, particularly lymphoproliferative disorders, and drugs, further complicating their clinical picture and management. Regarding new drugs, the false positivity of the Coombs test (direct antiglobulin test, DAT) following daratumumab adds to the list of difficult diagnosis, together with the passenger lymphocyte syndrome after solid organ transplants. Diagnosis of DAT-negative AIHAs and evaluation of disease-related risk factors for relapse and mortality, notwithstanding improvement in diagnostic approach, are still an unmet need. Finally, AIHA is increasingly described following therapy of solid cancers with inhibitors of immune checkpoint molecules. On the whole, the double-edged sword of new pathogenetic insights and therapies has changed the landscape of AIHA, both providing enthusiastic knowledge and complicating the clinical management of this disease.